The Impact of Personalized Learning Strategy on Improving the Performance of Firelighting and Firefighting Skills among Advanced Guides - Khaleel, Mohammed (Indonesian Journal Publisher, 2025)
The research aims to identify the impact of using the personal learning strategy on improving the performance efficiency of advanced female guides in fire-lighting and extinguishing skills. The researcher adopted the experimental approach due to its suitability to the nature of the research. The sample was selected from the guidance group for sports and scouting activities in Diyala Governorate, and numbered (24) advanced female guides. They were divided into two equal groups: one experimental group trained according to the personal learning strategy, and the other a control group that received training using the traditional method. Practical tests were used to measure the level of performance in the skills of fire-lighting and extinguishing. After statistically processing the data, the results showed statistically significant differences in favor of the experimental group, indicating the effectiveness of the personal learning strategy in developing the skill performance of advanced female guides. The research concludes that adopting modern educational strategies contributes to improving performance efficiency and developing scouting skills. The researcher recommends employing this strategy in various guidance training programs.